2010
DOI: 10.1016/j.foodchem.2009.09.073
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic profiles, antioxidant activity and in vitro antiviral properties of apple pomace

Abstract: a b s t r a c tMethanolic and acetonic extracts of apple pomace were evaluated for phenolic profiles, antioxidant properties and antiviral effect against herpes simplex virus type 1 (HSV-1) and 2 (HSV-2). Acetone extraction yielded the higher amounts of phenolic compounds. The extraction method influenced the phenolic composition although antioxidant activity correlated weakly with phenols concentration. Among the polyphenols analysed, quercetin glycosides were the most important family, followed by dihydrocha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
138
1
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 210 publications
(159 citation statements)
references
References 25 publications
15
138
1
5
Order By: Relevance
“…Polyphenol concentrations were twice as high in blackcurrant and strawberry pomaces than in apple pomace. Similar results were reported by other authors (Suarez et al 2010;Jaroslawska et al 2011) who found that polyphenol concentrations in fruit pomace are proportional to the polyphenol content of fresh fruit, and that berries are more abundant in polyphenols than apples (Perez-Jimenez et. al.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Polyphenol concentrations were twice as high in blackcurrant and strawberry pomaces than in apple pomace. Similar results were reported by other authors (Suarez et al 2010;Jaroslawska et al 2011) who found that polyphenol concentrations in fruit pomace are proportional to the polyphenol content of fresh fruit, and that berries are more abundant in polyphenols than apples (Perez-Jimenez et. al.…”
Section: Discussionsupporting
confidence: 91%
“…The antioxidative potential of pomaces correlated with their polyphenol content. In other studies, similar correlations were reported in apple, currant and strawberry pomaces (Sikora et al 2007) and in pomaces made from different apple varieties (Suarez et al 2010). In this experiment, the antioxidant activity of seedless strawberry pomace was more than two-fold higher that that of strawberry pomace.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This was particularly evident for the Panaia-red by-product, which contained about a 1.3, 1.9 and 1.9 times higher concentration of TP, TF and F3Os than Golden Delicious, respectively (table II). The range of concentrations of phenolic classes determined in Panaia-red and Golden Delicious pomace was generally consistent with previous reports in the literature, even if referring to different cultivars [6,41,42].Ćetković et al [41] reported a lower amount of TF in their apple pomace samples, as they reported values between 0.45 ± 0.02 and 1.19 ± 0.06 mg g −1 DM, while we found 11.0 ± 3.1 and 3.8 ± 0.6 mg g −1 DM, respectively, for Panaiared and Golden Delicious pomace. The dry matter contents of the two varieties' pomace were not significantly different and constituted 20.4% and 21.4%, respectively, for Panaia-red and Golden Delicious.…”
Section: Apple Juice and Pomace Phenolic Concentrationsupporting
confidence: 90%
“…To date, the major class of compounds identified in AP are flavonoids, where flavonols are the largest sub-class followed by flavanols, flavanones, flavones, dihydrochalcones and anthocyanins. The phenolic acids identified are primarily hydroxycinnamic acid derivatives and lesser of hydroxybenzoic acids (Cam & Aaby, 2010;Cetkovic et al, 2008;Diñeiro García, Valles, & Picinelli Lobo, 2009;Foo & Lu, 1999;Lu & Foo, 1997, 2000Sanchez-Rabaneda et al, 2004;Schieber et al, 2003;Suárez et al, 2010).…”
Section: Introductionmentioning
confidence: 99%